Analisi Genital Hygiene Kejadian Flour Albus Patologis - Wardawati, Wardawati; Sumiati, Sumiati (Jurnal Kesehatan Nusantara (JKN), 2025)
Genital hygiene refers to female efforts to maintain intimate area cleanliness through habits like using clean water, washing from front to back, selecting proper materials, using safe feminine products, and changing pads regularly during menstruation. Pathological flour albus is abnormal vaginal discharge with changes in color, odor, texture, volume, and discomfort. This qualitative study with a phenomenological approach explores genital hygiene practices among female Public Health students at STIKes Bina Bangsa Majene experiencing pathological flour albus. Four students and one lecturer were selected purposively as informants. Data were collected through interviews, observation, and documentation, and analyzed using the Miles and Huberman model. Results showed varied hygiene practices: some used clean running water and correct washing methods, while others used stagnant water, washed incorrectly, or chose inappropriate products. All informants reported symptoms such as thick yellowish discharge, unpleasant odor, and discomfort. Inadequate hygiene may contribute to pathological flour albus. Promoting proper hygiene education is essential